2019
DOI: 10.1097/prs.0000000000005723
|View full text |Cite
|
Sign up to set email alerts
|

CLEFT-Q: Detecting Differences in Outcomes among 2434 Patients with Varying Cleft Types

Abstract: Background: Measuring the patient perspective is important in evaluating outcomes of cleft care. Understanding how treatment outcomes vary depending on cleft type may allow for better planning of treatments, setting of expectations, and more accurate benchmarking efforts. The CLEFT-Q is a patient-reported outcome measure for patients with cleft lip and/or palate. Methods: The 12 CLEFT-Q scales measuring appearance (i.e., face, nose, nostrils, lips, clef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
4
22
0
1
Order By: Relevance
“…It has been demonstrated that participants with less complex cleft types (incomplete uCLP or CP only) have better speech outcomes than those with more complex cleft types (complete uCLP or bCLP). 26 Participants who had speech therapy are also likely have better speech than those who had no therapy. Thus, it is hypothesized that the English SLPs may have had improved accuracy evaluating participants with less severe speech pathology because they did not have to overcome the dual challenges of the unfamiliarity of the language and disordered speech.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that participants with less complex cleft types (incomplete uCLP or CP only) have better speech outcomes than those with more complex cleft types (complete uCLP or bCLP). 26 Participants who had speech therapy are also likely have better speech than those who had no therapy. Thus, it is hypothesized that the English SLPs may have had improved accuracy evaluating participants with less severe speech pathology because they did not have to overcome the dual challenges of the unfamiliarity of the language and disordered speech.…”
Section: Discussionmentioning
confidence: 99%
“…O autorrelato de pacientes com FLP pode variar de acordo com idade, sexo, tipo de fissura (Riff et al, 2019;Klassen et al, 2018) e o tipo de tratamento (Papi et al, 2015;Eckstein et al, 2011) estes achados e indicam o tratamento cirúrgico como modulador da qualidade de vida de pacientes com fissura (Broder et al, 2017;Belluci & Genaro 2016). Estudos evidenciam que os tratamentos das FLP melhoraram significativamente o bem-estar funcional e emocional, a autoestima e interação social, bem como o funcionamento físico e psicológico e, impactam positivamente na condição de saúde bucal de pacientes (Broder et al, 2017;Belluci & Genaro, 2016;Eckstein et al, 2011).…”
Section: Discussionunclassified
“…Plastic and Reconstructive Surgery has published many articles outlining the development and validation of popular patient-reported outcome measures (Table 3). [50][51][52][53][54][55][56][57][58] One such measure, the BREAST-Q, was used to compare patient satisfaction and quality of life in patients undergoing unilateral and bilateral autologous breast reconstruction. 59 Using an 8-year follow-up, the authors concluded that satisfaction rates did not differ up to 3 years postoperatively; however, a "possible divergence" of satisfaction beyond this time was noted.…”
Section: Plastic and Reconstructive Surgery • May 2021mentioning
confidence: 99%